International Scientific Conference »Research and Education in Nursing: Book of Abstracts, September 29th, 2020, Slovenia - Marina Bajić; Pajnkihar, Majda; Čuček Trifkovič, Klavdija; Šostar Turk, Sonja; Štiglic, Gregor (2020)
University of Maribor Faculty of Health Sciences is organizing the Online International Scientific Conference »Research and Education in Nursing«. It will be held on September 29th 2020 at the faculty and e-proceedings of the conference will include most recent findings of domestic and foreign researchers and students in nursing and health sciences. The conference aims to explore advances in nursing research and education and it is intended for knowledge and experience exchange of participants about the impact of research on health care in Slovenian and international arena. It will provide an opportunity to promote the development, dissemination and use of knowledge in the field of nursing and health sciences for nursing practitioners and educators, furthermore they can exchange research evidence, models of best practice and innovative ideas.
Keywords: nursing; health sciences; conference; research; education